"St. Mary's Is Gay-Town": Girls' Perceptions of Same-Sex Sexual Behavior in Juvenile Residential Treatment. (June 2020) - Panfil, Vanessa R.; Peterson, Dana
Understanding lesbian, gay, or bisexual (LGB) girls' experiences in juvenile residential facilities is essential for working toward their fair and affirming treatment, but other girls' perceptions of "gay girls" in juvenile facilities also contribute to the treatment environment. Drawing from interviews with a sample of 59 girls in a juvenile residential treatment center serving delinquent, status offending, and maltreated youth in upstate New York, we explore girls' perceptions of same-sex sexual behavior in that setting to illuminate dynamics and their implications for treatment experiences. Opinions ranged from negative perceptions expressed by self-identified straight and LGB girls, to matter-of-fact descriptions that were more neutral, to positive affirmations sometimes containing anti-staff sentiments. These perceptions indicate the complicated nature and consequences of youth–youth and youth–staff interactions around this issue.